Feminism is... - Black, Alexandra; Buller, Laura; Hoyle, Emily; Todd, Megan (DK Penguin Random House Publishing, 2019)
Includes short biographies of Sojourner Truth, Emmeline Pankhurst, Gloria Steinem, Chimamanda Ngozi Adichie, Simone de Beauvoir, bell hooks, Judith Butler, Frida Kahlo, Malala Yousafzai, Audre Lorde, Alice Schwarzer, Rigoberta Menchú.